Evaporation heat transfer and pressure drop of low-gwp refrigerants in a horizontal tube. (February 2020) - Li, Zhaohua; Jiang, Hanying; Chen, Xinwen; Liang, Kun
Highlights: R152a has much higher evaporation heat transfer coefficient than R134a and R1234yf. R1234yf and R134a have similar evaporator pressure drop. A new evaporation heat transfer correlation was proposed. The new correlation for R1234yf, R152a and R134a has MAPE of 14%, 10% and 12%. The newly developed two-phase frictional pressure drop correlations are more accurate. Abstract: Pressure drop and heat transfer in evaporators have significant influence on the efficiency and capacity of vapour compression refrigeration (VCR) systems. Oil lubricant deteriorates the heat transfer and causes blockage in compact evaporators, particularly micro-channel. Experiments were carried out to investigate the evaporation heat transfer and pressure drop of R1234yf, R152a and R134a in an oil-free VCR system using a horizontal tube. The results show that R1234yf has the highest pressure drop and R152a has the highest heat transfer coefficient. Two existing correlations were improved based on experimental data to predict the Nusselt number and two-phase frictional pressure drop in evaporator for three refrigerants. The improved correlations were proposed as a function of annular diameter ratio, Reynolds number, Prandtl number, Martinelli parameter and Chisholm parameter. Overall the Mean Absolute Percentage Error for the improved correlations are lower than 16%. The present correlations can effectively be adopted for modelling VCR systems with high confidence to optimise the evaporator and predict the performance.